Qualitative research and theory development mystery as method - Alvesson, Mats, 1956- (SAGE, 2011)
Empirical data is one of the cornerstones of knowledge in the social sciences, and yet the researcher often takes it for granted, reserving his or her imaginative faculties for finding a theory that 'fits the data'. This revealing account of the theory-data relationship calls this faith in data into question and establishes a reflexive framework and vocabulary to explore the creative, political and philosophical elements of data production.